Uranyl Clusters Based on 1,10-Phenanthroline Derivative Ligands: Synthesis, Crystal Structures, and Iodine Capture - Men, Xiao-Feng; Kong, Xiang-He; Huang, Zhi-Wei; Fu, Xuan; Mei, Lei; Niu, Na; Hu, Kong-Qiu; Shi, Wei-Qun (Inorganic chemistry, 2025)
The clusters have garnered widespread interest owing to their captivating structures and their potential applications in diverse scientific disciplines. Within this study, we synthesized two uranyl clusters, (UO2)3(DMF)2(CO3)(bmpd)·DMF (IHEP-34) and (UO2)10(O)2(OH)2(CO3)2(btpd)2 (IHEP-35), by the utilization of 1,10-phenanthroline derivative ligands in conjunction with uranyl cations through solvothermal synthesis techniques. Both clusters are characterized by a V-shaped [(UO2)3(CO3)]4+ unit, whose configuration strikingly differs from the typical triangular [(UO2)3(O)]4+/[(UO2)3(OH)]5+ structures. Density functional theory calculations show that the [U3] cluster and [U10] cluster boast of remarkable stability with the HOMO–LUMO gap of 2.13 and 0.90 eV, respectively. The [U10] clusters in IHEP-35 are orderly assembled through weak intermolecular interactions, forming a 3D supramolecular porous structure, which exhibits an excellent performance in the adsorption of gaseous iodine. The maximum adsorption capacity of IHEP-35 for gaseous iodine is 1324 mg·g–1. The analysis of XPS and Raman spectra reveals that the adsorbed iodine in IHEP-35 predominantly exists in the form of a triiodide anion.